2015
DOI: 10.1515/ijdhd-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vibration on the quality of gait in women with cerebral palsy

Abstract: In contrast to a normal gait, the locomotion of people with infantile cerebral palsy (ICP) is characterized by great variability. An experiment was conducted to determine if the use of whole-body vibrations changes the time of support by each of the extremities as well as the range of flexion of the hip and knee articulations. Three women with ICP were involved in the whole-body vibration experiment. The parameters of the vibration adopted during training were a frequency of 20 Hz and an amplitude of 2 mm. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Myśliwiec et al found increased ROM in the knee joint but no change in the hip joint after 4 weeks of vertical WBV application in three female adults with spastic CP. 47 Yabumoto et al found a trend in their case report of an 8-year-old boy with CP (GMFCS level III) for improved ROM after a 5-week intervention of vertical WBV application complementing conventional physiotherapy. 63 Furthermore, Camerota et al observed increased passive ROM in the ankle joint and increased functional mobility in joints of the lower extremities during gait in a 1-month follow-up after 3-day focal vibration applied to the muscle belly of the triceps surae in a child with triplegic CP (GMFCS level II).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Myśliwiec et al found increased ROM in the knee joint but no change in the hip joint after 4 weeks of vertical WBV application in three female adults with spastic CP. 47 Yabumoto et al found a trend in their case report of an 8-year-old boy with CP (GMFCS level III) for improved ROM after a 5-week intervention of vertical WBV application complementing conventional physiotherapy. 63 Furthermore, Camerota et al observed increased passive ROM in the ankle joint and increased functional mobility in joints of the lower extremities during gait in a 1-month follow-up after 3-day focal vibration applied to the muscle belly of the triceps surae in a child with triplegic CP (GMFCS level II).…”
Section: Resultsmentioning
confidence: 97%
“…Long-term adaptations refer to chronic changes manifested after repeated sessions of VT executed over weeks or months. The duration of applied vibration ranges from 30 seconds 46 to 1, 47 49 3, 48 , 50 56 5, 57 9, 58 , 59 and 10 minutes, 36 , 60 with the number of sets ranging from one to six. A summary of methodological quality can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation